The Legal Status of Female Guardians in 1530s Lithuania - Kunsmanaitė, Jurgita (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2005)
As may be seen from the legal sources of the time, the institution of guardianship of children was fully formed in the Grand Duchy of Lithuania by the beginning of the 16th century. Both the First Lithuanian Statute of 15292 and the court cases of the Books of Court Records of the Lithuanian Metrica – that is, the collection of documents of the chancery of the Grand Duchy of Lithuania – provide various examples of guardianship, covering such questions as the choice and change of guardians, and their rights and obligations.